Travelling waves for low-grade glioma growth and response to a chemotherapy model - Bartłomiejczyk, Agnieszka; Bodnar, Marek; Bogdańska, Magdalena U.; Piotrowska, Monika J. (Zielona Góra: Uniwersytet Zielonogórski)
Low-grade gliomas (LGGs) are primary brain tumours which evolve very slowly in time, but inevitably cause patient death. In this paper, we consider a PDE version of the previously proposed ODE model that describes the changes in the densities of functionally alive LGGs cells and cells that are irreversibly damaged by chemotherapy treatment. Besides the basic mathematical properties of the model, we study the possibility of the existence of travelling wave solutions in the framework of Fenichel`s invariant manifold theory. The estimates of the minimum speeds of the travelling wave solutions are provided. The obtained analytical results are illustrated by numerical simulations.
Keywords: glioma; tumour; generalized model; treatment; partial differential equations; wave solutions; chemotherapy